Multiscale molecular dynamics simulations of lipid interactions with P-glycoprotein in a complex membrane - Domicevica, L; Koldsø, H; Biggin, P (Elsevier, 2017)
P-glycoprotein (P-gp) can transport a wide range of very different hydrophobic organic molecules across the membrane. Its ability to extrude molecules from the cell creates delivery problems for drugs that target proteins in the central nervous system (CNS) and also causes drug-resistance in many forms of cancer. Whether a drug will be susceptible to export by P-gp is difficult to predict and currently this is usually assessed with empirical and/or animal models. Thus, there is a need to better understand how P-gp works at the molecular level in order to fulfil the 3Rs: Refinement, reduction and replacement of animals in research. As structural information increasingly becomes available, our understanding at the molecular level improves. Proteins like P-gp are however very dynamic entities and thus one of the most appropriate ways to study them is with molecular dynamics simulations, especially as this can capture the influence of the surrounding environment. Recent parameterization developments have meant that it is now possible to simulate lipid bilayers that more closely resemble in vivo membranes in terms of their composition. In this report we construct a complex lipid bilayer that mimics the composition of brain epithelial cells and examine the interactions of it with P-gp. We find that the negatively charged phosphatidylserine lipids in the inner leaflet of the membrane tend to form an annulus around P-gp. We also observed the interaction of cholesterol with three distinct areas of the P-gp. Potential of mean force (PMF) calculations suggest that a crevice between transmembrane helices 10 and 12 has particularly favourable interaction energy for cholesterol.